The Role of the Patrol of the Samapta Unit of the Surakarta Police in Preventing the Abuse of Ciu Types of Alcoholic Drink - Mahadi Gandhi Davito Hutagaol (Advances in Police Science Research Journal, 2022)
As one of the state institutions in Indonesia, the National Police is tasked with maintaining security and public order. Various kinds of phenomena in society that add to the number of public order disturbances that occur, including the problem of alcohol abuse of the type of ciu. To overcome this, it is necessary to have preemptive efforts from the Police, especially the Surakarta Police, namely through the Surakarta Police Satsamapta with various kinds of activities such as Patrol. This Final Project discusses the problems that occur including how the role of the Surakarta Police Samapta Unit through the Patrol in preventing the abuse of ciu liquor and what efforts the Surakarta Police Samapta Unit through the Patrol to prevent the abuse of ciu liquor. The purpose of this study was to describe the role of the Surakarta Police Satsamapta patrol in preventing the abuse of ciu liquor and to describe and find efforts to increase the role of the Satsamapta patrol.As an analytical knife, the author uses management theory through 4 POAC functions and SWOT analysis theory, the concept of Patrol and Liquor. This final project uses a qualitative approach. The type of writing is field research while the data collection techniques are through interviews, observations, and document studies. For the data analysis technique, the writer uses data reduction, data presentation, and drawing conclusionsThe conclusion of this study was that the role of the implementation of Patrol activities by the Surakarta Police Samapta Unit was still not right on target due to various kinds of internal and external factors. Efforts are being made to increase the role of the Surakarta Police Satsamapta patrol, namely by adding or varying patrol routes and hours so that they are right on target.